Performance Assessment Tool for Transportation Infrastructure and Urban Development for Tourism - Diana Lisa (International Conference on Engineering and Technology Development (ICETD), 2012)
Policy development of urban transport system development should be directed to the realization of an integrated national transportation system, orderly, safe and comfortable, and efficient in supporting the mobility of people, goods and services, and supporting regional development, to be laid out and kept adjusted to economic development, the rate of technological progress , spatial policy, environment conservation, and national energy policy that will always be able to meet the needs and demands of community development. For the realization of a sustainable transport system, the following research as a basis for writing the policy in this regard goverment city bus transport Damri, who has made a regulation will be the availability of means of transport. Due to the limited fleet as well as distance and time long enough to reach into the study area, Damri bus used only for certain people only, so that people are not too dependent on this transport. Other reasons, communities average has had a personal vehicle. While people outside the study area not many people know. They use a private vehicle. The reason, many of them are not aware of the existence Damri bus transportation routes that pass, long wait, as well as other reasons.